PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN (Studi Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Priode Tahun 2016-2020) - Umar, Fifi Nurfitria; Hajar, Ibnu; Amstrong TN, Valentinus; Sujono, Sujono; Zaluddin, Zaluddin (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2023)
The source of data used in this study was secondary data. Twenty companies were selected using the purposive sampling technique. The data collection technique used in this study was the documentation method derived from the Indonesian Stock Exchange (IDX) gallery from 2016 to 2020. The data analysis was carried out by applying panel data regression (pooled data) technique. The result of this study found that 1) Self-financing Ratio (E/C), Financial Leverage Ratio (LR), Long-term Asset Ratio (LAR) had a negative and significant effect on Financial Performance, 2) Debt-to Assets Ratio (DAR) had a positive and significant effect on Financial Performance, 3) Financial Assets to Total Assets had a positive and insignificant effect on Financial Performance.